Astaxanthin supplementation enhances metabolic adaptation with aerobic training in the elderly. Issue 11 (10th June 2021) - Liu, Sophia Z.; Valencia, Ana P.; VanDoren, Matt P.; Shankland, Eric G.; Roshanravan, Baback; Conley, Kevin E.; Marcinek, David J.
Abstract: Endurance training (ET) is recommended for the elderly to improve metabolic health and aerobic capacity. However, ET‐induced adaptations may be suboptimal due to oxidative stress and exaggerated inflammatory response to ET. The natural antioxidant and anti‐inflammatory dietary supplement astaxanthin (AX) has been found to increase endurance performance among young athletes, but limited investigations have focused on the elderly. We tested a formulation of AX in combination with ET in healthy older adults (65–82 years) to determine if AX improves metabolic adaptations with ET, and if AX effects are sex‐dependent. Forty‐two subjects were randomized to either placebo (PL) or AX during 3 months of ET. Specific muscle endurance was measured in ankle dorsiflexors. Whole body exercise endurance and fat oxidation (FATox) was assessed with a graded exercise test (GXT) in conjunction with indirect calorimetry. Results: ET led to improved specific muscle endurance only in the AX group (Pre 353 ± 26 vs. Post 472 ± 41 contractions), and submaximal GXT duration improved in both groups (PL 40.8 ± 9.1% and AX 41.1 ± 6.3%). The increase in FATox at lower intensity after ET was greater in AX (PL 0.23 ± 0.15 g vs. AX 0.76 ± 0.18 g) and was associated with reduced carbohydrate oxidation and increased exercise efficiency in males but not in females. Abstract : Astaxanthin combined with endurance training promoted fat oxidation compared to training alone. Astaxanthin led to carbohydrate sparing and improved exercise efficiency especially in older males.